Pengaruh Pemberian Pupuk Organik Cair (POC) Keong Mas (Pomacea canaliculata L.) Terhadap Pertumbuhan Semai Cendana (Santalum album Linn.) - Imelda Maria Irmawasti Teku; Astin E. Mau; Norman P. L. B. Riwu Kaho; Muhamad Soimin (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
Sandalwood, scientifically known as Santalum album L., is a endemic plant from East Nusa Tenggara with significant economic values. This study aimed to determine the effect of applying liquid organic fertilizer from Golden Apple Snail (Pomacea canaliculata L.) on the growth of sandalwood seedlings. The study used a completely randomized design (CRD) with a single factor, consisting of four treatments: B0 (control), B1 (POC 10ml/ltr), B2 (POC 20ml/ltr), and B3 (POC 30ml/ltr), each with three replications. Further testing was conducted using Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results showed that the application of liquid organic fertilizer (POC) from Golden Apple Snail had a significant effect on the parameters of plant height, seedling diameter, number of leaves, fresh weight, and dry weight. These parameters showed the highest significant differences, respectively: 15.200 cm, 5.767 mm, 12.667 leaves, 1.233 g, and 0.933 g in the B3 treatment or the application of POC Golden Apple Snail at 30ml/ltr. Therefore, the golden apple snail liquid organic fertilizer can be used on plants at a concentration of 30 ml/liter.